The Role of Multimodality Imaging in Athlete’s Heart Diagnosis: Current Status and Future Directions - Antonello D’Andrea (MDPI AG, 2021)
“Athlete’s heart” is a spectrum of morphological and functional changes which occur in the heart of people who practice physical activity. When athlete’s heart occurs with its most marked expression, it may overlap with a differential diagnosis with certain structural cardiac diseases, including cardiomyopathies, valvular diseases, aortopathies, myocarditis, and coronary artery anomalies. Identifying the underlying cardiac is essential to reduce the potential for sudden cardiac death. For this purpose, a spectrum of imaging modalities, including rest and exercise stress echocardiography, speckle tracking echocardiography, cardiac magnetic resonance, computed tomography, and nuclear scintigraphy, can be undertaken. The objective of this review article is to provide to the clinician a practical step-by-step approach, aiming at distinguishing between extreme physiology and structural cardiac disease during the athlete’s cardiovascular evaluation.